2021
DOI: 10.1101/2021.02.18.431759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A covalently crosslinked bioink for multi-materials drop-on-demand 3D bioprinting of three-dimensional cell cultures

Abstract: In vitro three-dimensional (3D) cell models have been accepted to better recapitulate aspects of in vivo organ environment than 2D cell culture. Currently, the production of these complex in vitro 3D cell models with multiple cell types and microenvironments remains challenging and prone to human error. Here we report a versatile bioink comprised of a 4-arm PEG based polymer with distal maleimide derivatives as the main ink component and a bis-thiol species as the activator that crosslinks the polymer to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Storage modulus continued to increase over time, with 2.5%, 5% and 10% (w/v) final Gel-SH Gel-SH/PEG-4MAL hydrogels possessing storage moduli of 492 Pa, 1055 Pa, and 1863 Pa, respectively, 1 h post-crosslinking. The storage and loss moduli of the 2.5% (w/v) final Gel-SH Gel-SH/PEG-4MAL hydrogels were similar to values reported by Utama et al [25] for bis-thiol-PEG/PEG-4MAL hydrogels, where 5% (w/v) final PEG-4MAL bis-thiol-PEG/PEG-4MAL hydrogels possessed storage moduli of roughly 530 Pa. The maleimide-reactive hydrogel precursor used by Utama et al was dissolved at ~1% (w/v); therefore, accounting for the final concentration of both Gel-SH and PEG-4MAL in the prepared hydrogels, the total concentration of 2.5% (w/v) final Gel-SH Gel-hydrogels is most similar to the hydrogels reported by Utama et al These results indicated that although Michael-type addition between Gel-SH and PEG-4MAL forms 3D Gel-SH/PEG-4MAL matrices near-instantaneously, such matrices continue to crosslink over time.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Storage modulus continued to increase over time, with 2.5%, 5% and 10% (w/v) final Gel-SH Gel-SH/PEG-4MAL hydrogels possessing storage moduli of 492 Pa, 1055 Pa, and 1863 Pa, respectively, 1 h post-crosslinking. The storage and loss moduli of the 2.5% (w/v) final Gel-SH Gel-SH/PEG-4MAL hydrogels were similar to values reported by Utama et al [25] for bis-thiol-PEG/PEG-4MAL hydrogels, where 5% (w/v) final PEG-4MAL bis-thiol-PEG/PEG-4MAL hydrogels possessed storage moduli of roughly 530 Pa. The maleimide-reactive hydrogel precursor used by Utama et al was dissolved at ~1% (w/v); therefore, accounting for the final concentration of both Gel-SH and PEG-4MAL in the prepared hydrogels, the total concentration of 2.5% (w/v) final Gel-SH Gel-hydrogels is most similar to the hydrogels reported by Utama et al These results indicated that although Michael-type addition between Gel-SH and PEG-4MAL forms 3D Gel-SH/PEG-4MAL matrices near-instantaneously, such matrices continue to crosslink over time.…”
Section: Resultssupporting
confidence: 87%
“…For example, hydrogels are water-swollen polymeric networks, formed through the interaction of hydrogel precursors, that can provide suitable environments for 3D cell culture [ 22 , 23 ]. Poly(ethylene)-glycol (PEG)-based hydrogels are synthetic 3D cell culture matrices, produced through crosslinking of PEG-based hydrogel precursors [ 16 , 21 , 24 , 25 ] that can be produced with high batch-to-batch reproducibility, therefore addressing the cross-batch variability observed in BME matrices. Additionally, some PEG-based hydrogels can be mechanically tuned through variation of hydrogel precursor concentration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( H ) Photographs of hydrogel structures comprising different materials bioprinted using the high-end Inventia RASTRUM droplet-based machine (scale bars: 2 mm). Adapted from Utama et al 248 with permission from the corresponding author, Professor J. Justin Gooding, UNSW, Australia. Note: Due to the low viscosity of the bio-inks used with the droplet-based printers, it is difficult to print macroscopic 3D structures using these machines.…”
Section: Conclusion and Future Projections For Low-cost 3d Bioprinter Trendsmentioning
confidence: 99%
“…RASTRUM™ is a drop-on-demand high throughput bioprinter that can deposit cells and matrix components into common tissue culture microplates to form 3D cell culture 12 . High precision and delicate pressure regulation enables ejection of nanolitre volumes of different bioinks, which can be tuned to form hydrogels that match the mechanical and biochemical properties of different tissue types and provide a physiologically relevant matrix environment for cultured cells 13 . After printing, further culture handling, such as media exchange, treatment addition and sample preparation, is identical to 2D cell culture and thus provides a cost-effective way for 3D cell culture generation and maintenance.…”
Section: Introductionmentioning
confidence: 99%